UPAYA MENINGKATKAN PEMAHAMAN KONSEP PADA OPERASI HITUNG BILANGAN BULAT MELALUI METODE DEMONSTRASI BENDA KONKRIT DI KELAS IIIA SD NEGERI 100715 DESA TELO KEC. BATANGTORU - Sari, Mutia; Syahrani, Laila (IAIN PADANGSIDIMPUAN, 2018)
This research was conducted to help students understand the concepts learned and facilitate students in solving multiplication material questions. Because the ability to understand concepts is part of a high level of mathematical thinking skills. This research was carried out in the Public Elementary School 100715 in Telo Village, Kec. Batangtoru. This type of research is Class Action Research (CAR). This research was conducted in 2 cycles. Techniques for receiving data by supporting tests and observations. The subject of this study was class III ^ A Public Elementary School 100715 Desa Telo Kec. Batangtoru.The results of this study were in the first cycle of students who completed 11 students with an average score of 66.38 and the percentage of completeness was 55%. In Cycle II students who completed as many as 19 students with an average value of students of 82.13 and the percentage of completeness was 95%. Thus it means applying the method of discussion of concrete objects can increase students' understanding on the subject of multiplication in class III ^ A 100715 Public Elementary School, Telo Village, Kec. Batangtoru.